Antibiotic resistance profile and phenotypic detection of betaLactamase-producers among gram-negative bacteria isolated from (2016)
Background: Cockroaches are carriers of numerous microorganisms. However, there is paucity of information on their role as potential reservoir for beta-lactamase producers. Objectives: This research determined the antibiotics susceptibility profile of Beta-lactamase producing Gramnegative bacteria isolated from the gut of household cockroaches in selected locations in and around University of Ibadan, Oyo state. Materials and Methods: Thirty Cockroaches from different locations in and around University of Ibadan were collected between June 2015 and March, 2016, and their intestinal homogenates cultured on different selective media for the isolation of bacteria. The isolates were identified using a combination of biochemical tests and 16S rRNA sequencing. Antibiotic susceptibility testing was done using the disc-diffusion technique and phenotypic detection of extended-spectrum beta-lactamase (ESBL), AmpC-beta-lactamase (AmpC) and Metallo-beta-lactamase (MBL) production was done using double-disc synergy, cefoxitin/cloxacillin and imipenem/EDTA double-disc methods respectively. Results: A total number of 58 bacteria belonging to nine genera; Pseudomonas, Proteus, Klebsiella, Salmonella, Enterobacter, Escherichia, Serratia, Shigella and Raoultella were isolated. Higher percentage of the isolates exhibited resistance to erythromycin (90%), azithromycin (87.5%), amoxicillin (84.5%), ampicillin (74.1%), amoxicillin-clavulanic acid (74.1%), cefoxitin (67.2%) and chloramphenicol (54%), while lower percentage showed resistance to aztreonam (25%), ertapenem (13%), cefotaxime (8.6%), ceftazidime (10.3%), cefepime (5.2%), ciprofloxacin (3.5%), gentamicin (5.2%) and imipenem (0%). MDR phenotype was recorded among 82% of the isolates, 17.2% were positive for ESBL, 12% for AmpC and 13.8% for MBL production. Conclusion: This study identified household cockroaches Periplaneta americana, as a potential reservoir for MDR and beta-lactamase-producing isolates. Keywords: Susceptibility testing, ESBL, AmpC, MBL, Beta-Lactamase, MDR, Household cockroaches Cockroaches are insects of the order Blattodea some of which are associated with human environment (Beccaloni, 2014). One of the two species of cockroaches that has been reported by different authors to be widely distributed in Nigeria is the American cockroaches namely Periplaneta americana (Ajero et al., 2011; Etim et al., 2012; Akinjogunla et al., 2012; Tilahun et al., 2012). The incidence of Cockroach infestation in restaurants, hospitals, warehouses, offices and within households, particularly the kitchen, have been reported to be very high in Nigeria (Omudu and Akosu, 2013; Braimah et al., 2015). The insects being nocturnal in nature are found in dark places within the households during the day hiding in opened and cracked sections of the wall, furniture, inside wardrobes and cupboards (Omudu and Akosu, 2013; Billah et al., 2015; Braimah et al., 2015). Sometimes they enter into cooking pots and other kitchen utensils if left opened. They feed on leftover food, cooked and uncooked food materials contaminating them with microorganisms on their body and in their faecal droppings especially those ready to eat food that do not require further processing before eating them (Xue et al., 2009). They are also found in other parts of the house including bedrooms (Etim et al., 2013). Cockroaches are also found in garbage and sewage tanks, particularly in homes with pit latrine (Craczyk et al., 2005; Pai et al., 2005) making them a potential vector for pathogenic and non-pathogenic microorganisms from human origin (Graczyk et al., 2005; Pai et al., 2005; Vazirianzadeh et al. 2014). Studies have shown that most of the disease-causing bacteria of human origin can survive within the body system of cockroaches (Imamura et al., 2003), hence their presence in sewage and garbage elucidate their role as potential carriers of these human diseasecausing agents (Vazirianzadeh et al., 2014). Several authors have incriminated cockroaches as reservoir and transmitters of disease-causing microorganisms like Enterobacter spp., Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Shigella spp., Campylobacter spp. and Salmonella spp., especially those in the hospital environment (Craczyk et al., 2005; Tatfeng et al., 2005; Ukay et al., 2009; Tilahun et al., 2012; Vazirianzadeh et al., 2014). In addition, cockroaches have also been reported to carry microbial agents of leprosy, urinary tract infection (Enterococcus spp.), MATERIALS AND METHODS Study Area The study was carried out in University of Ibadan metropolis, Oyo state. The areas of choice were kitchen and toilets in residential apartments in and around the University of Ibadan. Specimen Collection and Preparation for bacteria isolation A total of 30 cockroaches, identified to be Periplaneta americana, through online file (Beccaloni, 2014), were collected from residential cholecystitis (Helicobacter hepaticus), plague (Yersinia pestis) and bacteremia, septic arthritis and peritonitis (Oligella urethralis) (Pat, 2006; Falsafi and Mahboubi, 2013). Antibiotic resistance and its spread among bacterial isolates is a global problem and has been reported among bacterial isolates in both clinical and community settings (WHO, 2014). Cockroaches have been reported to harbour pathogenic and opportunistic pathogens that exhibited high level resistance to antibiotics, especially those used in lifethreatening disease cases such as the cephalosporins and carbapenems (Fathpour et al., 2003; Bouamama et al., 2010; Wannigama et al., 2014). Bacterial isolates exhibiting multidrug resistance phenotype have also been reported in cockroaches (Devi and Murray, 1991; Tetteh-Quarcoo et al., 2013). Resistance to beta-lactam antibiotics are known to be mediated mostly by beta-lactamase enzymes. The initial variants of these enzymes were active only on the penicillin class but the discovery of the third generation cephalosporin class help to overcome their destructive action (Paterson and Bonomo, 2005). The advent of extended-spectrum beta-lactamase, and metallo beta-lactamase enzymes among others which are known in addition to the penicillin class, to hydrolyze the third generation cephalosporins (Ceftazidime, cefotaxime, ceftriaxone) and the carbapenems (imipenem, ertapenem) respectively, created a serious problem for clinicians in the management of life-threatening infections caused by such bacteria habouring the enzymes (Paterson and Bonomo, 2005). Currently, there is paucity of information on the various resistant determinants harboured by bacteria isolated from household cockroaches. This study therefore, aimed at using phenotypic techniques to determine multidrug resistance phenotype and the presence of common beta-lactamase enzymes among bacterial isolates from the gut of house-hold cockroaches in selected locations in and around University of Ibadan. apartments using sticky rods and direct collection with sterile hand-gloves (Paul et al., 1992). They were introduced into separate sterile wide-mouth bottles aseptically and transported to the laboratory of the Department of Pharmaceutical Microbiology, University of Ibadan for freezing at 0oC for 10- 15min to anaesthetize them. Intestinal gut of each cockroach was prepared into samples using the method highlighted by Tetteh-Quarcoo et al. (2013)